A Case Study on Differential Diagnosis of Episodic Left Arm Numbness. (2nd October 2021) - Shugan, Adam
ABSTRACT: According to the World Health Organization, cardiovascular disease is the number one cause of death globally. Cardiac-related maladies are a common occurrence in emergency rooms across the United States. The most common symptoms of a myocardial infarction include pain or discomfort in the arms, left shoulder or elbows. Sometimes, what appears to be common, stereotypical symptoms could pose more than one diagnosis to a medical professional. This report describes the case of a 67-year-old male who presented to the emergency department with left arm numbness and syncopal episodes. He had a history of cardiac-related issues, which led to a concern for possible heart failure. Fortunately, an EEG was performed, revealing multiple right centroparietal dominant seizures.